CORPORATE SOCIAL RESPONSIBILITY (CSR) STRATEGY AS A LEGAL INSTRUMENT TO IMPROVE COMPANY REPUTATION - Gandhi Pharmacista (Jurnal Ekonomi, 2023)
Legal problems regarding inconsistencies in legislation regarding corporate social responsibility in Indonesia, which do not yet fully regulate the mechanism for implementing corporate social responsibility, and do not regulate clear sanctions. This research uses a qualitative method where the qualitative method aims to obtain a complete picture of a matter according to the views of the people being studied, while the aim of this research is to try to explain corporate CSR law based on plans and expected impacts and the results explain the reasons for corporate social responsibility regulations. the inconsistency of Indonesia being a free, sovereign country, including making regulations in the field of corporate social responsibility; environmental conditions are increasingly worrying, companies also become part of society; not all companies carry out their responsibilities. Second, Legal Certainty of the Mechanism for Implementing Corporate Social Responsibility. Third, sanctions should also be regulated, namely criminal sanctions so that corporate social responsibility will be adhered to as a legal obligation.